Comparison of Postoperative Duration of Analgesia in Patients Receiving Supraclavicular Brachial Plexus Block with and without Dexmedetomidine - Anum Zeb, Iqra Latif, Muhammad Khalid, Muhammad Arsalan Zahid, Muhammad Abdul Rahman Afzal, Abdul Sattar Shamasddin, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: For upper-limb orthopaedic surgery, supraclavicular brachial plexus block is routinely used and involves administering bupivacaine to the supraclavicular plexus. Recent studies claimed that the addition of dexmedetomidine to bupivacaine for supraclavicular brachial plexus block significantly prolonged the mean duration of postoperative analgesia. This study was necessitated by the fact that existing evidence was limited and there was no local published material to support the findings. Objective: The objective of this study was to compare the postoperative duration of analgesia in patients receiving supraclavicular brachial plexus for upper limb surgeries block with and without dexmedetomidine. Methods: This study was performed at the Department of Anesthesiology Lahore General Hospital, Lahore using randomized controlled trial. In this study, sixty patients between the ages of 18 and 60 and from both genders who underwent ultrasound-guided supraclavicular brachial plexus block for upper limb orthopedic surgery were randomly and equally divided into two treatment groups. The patients of Group-A received bupivacaine along with dexmedetomidine while those in Group-B received bupivacaine with normal saline for the block. Mean postoperative analgesia duration in minutes up to a VAS > 3 was the outcome variable. Each patient signed informed consent before the study. Results: The patients' average age was 38.4±14.1 years and 37 (61.7%) were male and 23 (38.3%) were female. The significantly longer mean duration of postoperative analgesia (754.27±144.89 vs. 441.80±111.38 minutes with p-value less than 0.001) was observed in patients receiving dexmedetomidine in addition to bupivacaine as compared to bupivacaine alone. This significant mean duration was also recorded in various subgroups of age, gender, BMI, and duration of surgery. Conclusion: The superiority of the combination of dexmedetomidine with bupivacaine was reported as compared to the conventional practice of bupivacaine alone in terms of significantly prolonged mean duration of postoperative analgesia. This novel combination may reduce the need for postoperative opioids and recommend it for future anesthetic practice. Keywords: Supraclavicular Brachial Plexus Block, Dexmedetomidine, Post-Operative Analgesia